CUSTOMARY COMMUNITIES IN THE ESTABLISHMENT OF VILLAGE CUSTOMARY INSTITUTIONS AS AN ALTERNATIVE DISPUTE SETTLEMENT - Yosefina Daku; Kornelius Yosep P.Meka; Adrianus Keriama Jawan (Sean Institute, 2023)
The existence of law accommodates every interest so that there is no conflict in society. From the statement we see the function of law as a mediator between many interests, one of which is the interests of indigenous peoples. Awareness of the importance of resolving customary law issues encourages the government to form institutions responsible for resolving customary law. The statement of recognition by the state to customary law communities is as long as they are still alive in the provisions of Article 18 paragraph (2) of the 1945 Constitution of the Republic of Indonesia becomes a question whether this article can be interpreted as a form of guarantee of full legal protection for customary law communities. This research discusses the existence of customary law communities in the formation of village customary institutions as alternative dispute resolution institutions. This type of normative legal research is studied through literature studies using legal materials collected through inventory and identification of laws and regulations. The approach used in this research is a statutory approach. The results of this study found that the existence of a customary law community unit and recognition from the local government through a regional regulation is a form of legal certainty for customary law communities in the region. With this recognition, the customary institution formed must come from the community unit which better understands the origin and traditional rights of the community so that the LAD is also a judicial institution at the indigenous community level is expected to be able to provide benefits to the community. Alternative dispute resolution is a concept of a customary law settlement process directed at an opportunity for parties to produce a win-win solution (win for all parties to the dispute) through negotiation, negotiation, mediation, arbitration and through the courts.